Changes in rubber due to its interaction with bitumen when producing asphalt rubber - Peralta, Elvira Joana Ferreira (2010)
The negative impact of the used tires residues can be reduced by reusing their rubber as a constituent of asphalt rubber (AR) mixtures, thus contributing for a sustainable development of road infrastructures. However, the increasing demands on the durability of pavements require a deeper knowledge about the physicochemical changes of the AR binders. The main objective of this research is to characterize the influence of bitumen in the rubber morphology and the changes in the density of bitumen, rubber and AR during its production. Four base bitumens interacted with crumb rubber in order to produce AR binders, which were then separated by using a modified "basket drainage method". The changes in rubber were studied through microscopy, swelling and depolymerization tests. It was concluded that i) the rubber particles swelled 250% their weight, but only increased 2.5% their equivalent diameter; ii) rubber particles can swell till saturation after interacting with softer bitumens; iii) re-vulcanization and re-polymerization among the rubber particles can eventually occur.